Empresas e direitos humanos: uma análise das violações de direitos elementares trabalhistas na Indústria da moda - Julianna do Nascimento Hernandez (2018)
The aim of the research is to analyze whether the UN Human Rights System is sufficient to appease human and labor rights violations suffered by workers of transnational corporations in the textile and clothing sector, especially after the productive restructuring that took place after 1970. It is noted that the international standards issued by the United Nations and the International Labor Organization set minimum global standards for decent work, without, however, having coercive norms to enforce States and transnational corporations. Thus, recent UN guidelines, such as the 2008 Framework and the 2011 Guiding Principles, as soft law, are also flawed in providing a regulatory environment of greater protection to the worker. The research reveals, above all, that the production structure of the Fashion Industry blatantly benefits from the lack of international social norms that apply directly and bindingly to corporations. Thus, by decentralizing its production through outsourcing and faction contracts, the practice, inserted in a context of "globaritarism", implies the extreme deregulation of the set of labor norms conquered during the nineteenth, twentieth and twentyfirst centuries, without the possibility of responsibility for the negative impacts on people and the environment.